The performance of credit rating systems in the assessment of collateral used in Eurosystem monetary policy operations - François Coppens; Fernando Gonzáles; Gerhard Winkler (National Bank of Belgium, 2007)
The aims of this paper are twofold: first, we attempt to express the threshold of a single “A” rating as issued by major international rating agencies in terms of annualised probabilities of default. We use data from Standard & Poor's and Moody's publicly available rating histories to construct confidence intervals for the level of probability of default to be associated with the single “A” rating. The focus on the single A rating level is not accidental, as this is the credit quality level at which the Eurosystem considers financial assets to be eligible collateral for its monetary policy operations. The second aim is to review various existing validation models for the probability of default which enable the analyst to check the ability of credit assessment systems to forecast future default events. Within this context the paper proposes a simple mechanism for the comparison of the performance of major rating agencies and that of other credit assessment systems, such as the internal ratings-based systems of commercial banks under the Basel II regime. This is done to provide a simple validation yardstick to help in the monitoring of the performance of the different credit assessment systems participating in the assessment of eligible collateral underlying Eurosystem monetary policy operations. Contrary to the widely used confidence interval approach, our proposal, based on an interpretation of p-values as frequencies, guarantees a convergence to an ex ante fixed probability of default (PD) value. Given the general characteristics of the problem considered, we consider this simple mechanism to also be applicable in other contexts.
Keywords: G20; G28; C49; 330; credit risk; rating; probability of default (PD); performance checking; backtesting; Kreditrisiko; Kreditwürdigkeit